Growth optimization, antibiogram, and molecular identification of Bacillus species isolated from the human gut: Identification of Bacillus species isolated from the human gut - Ullah, Rahim; Ali, Farooq; Ahmed, Shehzad; Ghazanfar, Shakira; Ahmad, Shahbaz; Aziz, Tariq; Al-Asmari, Fahad; Alamri, Abdulhakeem S.; Alhomrani, Majid; Shakeela, Qismat (Cellular and Molecular Biology, 2024)
The human microbial flora is quite diverse and versatile, playing several beneficial roles in association with the host and deriving nutrition from it. The present study aimed to identify gut microbial flora with potential probiotic activities. Eighteen bacterial isolates were screened from ten male individuals in this study. Seven bacterial isolates, NCCP-2046, NCCP-2031, NCCP-2035, NCCP-2040, NCCP-2041, NCCP-2044, and NCCP-2046, were isolated from the gut samples of volunteer men belonging to various areas of Rawalpindi and Islamabad. These bacterial isolates were cultured on De Man Rogosa and Sharpe Media (MRS), Tryptone Soya Agar (TSA), and Nutrient agar, which showed efficient bacterial growth. The morphological and biochemical characteristics of these bacterial strains were studied under their optimal growth conditions, along with molecular investigations. The antibiotic sensitivity pattern was tested using Kirby-Bauer method, which verified the higher MIC against all eight antibiotics used except for oxacillin. Phylogenetic analysis of only four bacterial isolates was performed based on their 16S rRNA sequences, and their top-hit sequence similarities in NCBI and EzBioCloud.net (95-98% and 94%) verified that these bacterial candidates belong to the Priestia and Staphylococcus genera. Based on molecular evidence through phylogeny and sequence similarities with previously defined bacterial candidates, the bacterial strains MG-461621 (NCCP-2031), MG-461622 (NCCP-2035), and MG-561934 (NCCP-2046) are presumed to be members of Priestia or novel species/genera, while MG-461623 (NCCP-2039) is also found to be a previously identified species of Staphylococcus. However, due to decreased similarity with the top-hit sequences, it could also be presumed to represent a member of a novel genus.